(untitled) (International Seven Journal of Health Research, 2025)
Objective: To evaluate the effectiveness of zinc supplementation in the treatment of acute diarrhea in children, focusing on reducing severity, and duration and preventing new episodes. Methods: This is a literature review, using the Google Scholar, PUBMED, Scielo, and LILACS databases together with information from Manuals and Guides of the World Health Organization and Ministry of Health, obtaining 24 articles. Bibliographic Review: Acute diarrhea, characterized by three or more liquid bowel movements in 24 hours, is one of the main causes of infant mortality, especially in developing countries. Several studies show zinc supplementation as an effective measure in reducing the duration and severity of diarrheal episodes in childhood, in addition to preventing recurrences. In addition, its use appears to decrease the frequency and duration of bowel movements and reduce hospitalizations. In addition to its use in acute diarrhea, there appear to be benefits in cases of pneumonia and malaria. Although effective, mild adverse effects, such as vomiting, reduce treatment adherence, and further studies are needed to assess the minimum dose required. Conclusion: Zinc supplementation, recommended by the WHO since 2004, reduces the severity and duration of diarrhea in children. However, research is possible to improve the dose and minimize adverse effects.